Automated irrigation management system for tree species seedlings using weighing mini-lysimeters - de Carvalho, Daniel Fonseca; da Costa, Gabriela Rodrigues; Conforto, Bruno Antônio Augusto Faria; Pinto, Marinaldo Ferreira; da Silva, Magali Ribeiro [UNESP] (Italian Society of Sivilculture and Forest Ecology (SISEF), 2024)
Due to the lack of irrigation management techniques, the application of water in forest nurseries is generally carried out without control, resulting in great waste. This study aimed to develop and evaluate weighing mini-lysimeters (ML) to automate the irrigation system and determine the water demand and evaluation of the initial tree species seedling growth. The structure was built out of wood to fit a tray of 54 tubes measuring 280 cm³. It was equipped with a load cell with a nominal capacity of 10 kg, located in the center of the structure. The mass variations of the set were recorded on a micro SD card using an Arduino Mega board, which allowed for the automated irrigation management system through an algorithm. Two MLs were built, determining the water demand of Dalbergia nigra (DN) and Enterolobium contortisiliquum (EC) seedlings in the initial growth phase. After calibration, the MLs presented an absolute error and mean squared error below 1% of the total mass, allowing effective irrigation control. During the evaluation period, 1.47 L seedling-1 of DN and 1.45 L seedling-1 of EC were applied, reaching 89 days after emer-gence, height and stem diameter of 39.2 cm and 3.4 mm, and 19.3 cm and 4.6 mm, respectively. The weighing mini-lysimeters developed demonstrated the ability to automate the irrigation of tree species seedlings, reducing the amount of water applied in forest nurseries.
Keywords: Brazilian rosewood; Dalbergia nigra; Enterolobium contortisiliquum; Evapotranspiration; Mini-lysimeters; Nursery; Pacara earpod tree